2019
DOI: 10.2355/isijinternational.isijint-2018-815
|View full text |Cite
|
Sign up to set email alerts
|

Addition Effect of Aromatic Amines on Coal Fluidity and Coke Strength

Abstract: BackgroundToday, high-strength coke is actively pursued to operate blast furnace with low reducing agent. 1) Caking properties are the important parameters in coal blending techniques to produce high-strength coke. 2) In particular, Gieseler plastometer method standardized by JIS M8801 have long been used for measuring 'fluidity' as caking properties. On the other hand, recently, the amount of high-quality coal with high fluidity has been limited. The tight supply and rising price of high-quality coal with hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…20) In the previous study, changes in the fluidity of coal were investigated when several hydrocarbon reagents were used. For example, polycyclic aromatic hydrocarbons, 21) aromatic hydrocarbons containing nitrogen, [21][22][23][24] and aromatic hydrocarbons containing oxygen. 21,25) These investigations revealed that the fluidity of coal increased when a PAH with a high boiling point or an aromatic hydrocarbon containing nitrogen was used, but decreased when an aromatic hydrocarbon containing oxygen was used.…”
Section: Introductionmentioning
confidence: 99%
“…20) In the previous study, changes in the fluidity of coal were investigated when several hydrocarbon reagents were used. For example, polycyclic aromatic hydrocarbons, 21) aromatic hydrocarbons containing nitrogen, [21][22][23][24] and aromatic hydrocarbons containing oxygen. 21,25) These investigations revealed that the fluidity of coal increased when a PAH with a high boiling point or an aromatic hydrocarbon containing nitrogen was used, but decreased when an aromatic hydrocarbon containing oxygen was used.…”
Section: Introductionmentioning
confidence: 99%